Perfil de mães e o desfecho do nascimento prematuro ou termo - Teixeira, Gracimary Alves (2015)
The birth or delivery under 37 weeks of pregnancy is considered a global public health problem, since it is seen as one of the main risk factors for neonatal morbidity and mortality, particularly in the first week of life. This study had the objective of analyzing the profile of mothers of premature and full-term babies for the outcome of birth. This is an analytical-descriptive and cross-sectional study, with a sample of 109 mothers of all the premature babies and 135 mothers of the randomly selected full-term babies, by drawing, occurred in the period from April to September 2015, in a public maternity. Data were organized on Microsoft Excel 2013; subsequently, there was the analysis of the analytical-descriptive statistics, through Statistica 10, through which the frequencies, proportions, p values, with 5% significance level, through the Chi-square test, were identified. The project was submitted to the Research Ethics Committee of the Federal University of Rio Grande do Norte, receiving a favorable opinion (nº 1047431/2015). This study has enabled us to identify that the socioeconomic profile of mothers of premature and full-term babies showed, in both, low schooling level and low income. In addition, our data point out in the two groups, before and during pregnancy, a high prevalence of sedentariness; statistical significance for overweight and obesity before and during pregnancy, with 42,22% prevalence before pregnancy of mothers of premature babies and 48,62% of mothers of full-term babies; with high blood pressure during pregnancy in 32,11% of mothers of premature babies and 17,04% of mothers of full-term babies. Moreover, pregnancy was only planned in 33,33%, and also unwanted by 21,1% of mothers of premature babies, while 40,37% of mothers of full-term babies planned pregnancy and 17,78% had unwanted pregnancy. With respect to the aggravating factor “illicit drugs”, there was consumption during pregnancy on the part of 8,26% of mothers of premature babies. The most frequent complications were: vaginal bleeding (in 43,12% of mothers of premature babies and 20% of mothers of full-term babies); urinary infection (in 44,95% of mothers of premature babies and 40% of mothers of full-term babies); and stressful pregnancy (in 62,96% of mothers of premature babies and 47,41% of mothers of full-term babies). Accordingly, babies were born with health problems in 58,10% of premature births and there was healthy birth in 96,30% of full-term babies. Therefore, the profile of mothers with obesity and overweight, unwanted pregnancy, user of illegal drugs during pregnancy, stressful pregnancy and vaginal bleeding may be associated with the birth of premature baby as unfavorable and hazardous event for the child’s health.